Enhancing Social Qualities in University Campus Outdoor Spaces through Islamic Spatial Configurations: The Case of the American University in Cairo - Kamel I. Abu Elkhair; Alaa ElDin Nagy Sarhan; Amr A. Bayoumi (Buildings, 2023)
Universities are under more pressure than ever before to attract more students and move up in rankings. Due to bounded space and rising plot values in city areas, a spatial configuration that meets user needs has become a very important topic for well-prepared and spatially suitable educational settings. However, today there is a rapid pace in the establishment of universities in Egypt. Insufficient use of university campus outdoor spaces (UCOS) is considered one of the main negative impacts on social quality in these universities in Egypt. This study aims to evaluate the social qualities according to the Islamic spatial configurations of UCOS in The American University in Cairo (AUC). The research is based on using integrated observational and computational methods in different UCOS. Observational methods are applied through behavioral mapping and movement tracing. Computational methods are applied through space syntax software. The AUC campus is selected as a case study because its design is based on different types of UCOS. The methodology follows three successive steps. Firstly, a field observation of the most used UCOS was undertaken. Secondly, a spatial analysis examining the potential effect of the campus spatial configuration was conducted. Finally, a comparative analytical approach that illustrates the relationship between Islamic spatial configurations of UCOS and activity categories according to user behaviors was taken. The research shows the considered types of UCOS and their ranking according to the observational and computational methods that achieve the highest values for social qualities.